2019
DOI: 10.1002/zaac.201900209
|View full text |Cite
|
Sign up to set email alerts
|

The Water‐Rich Iodidobismuthate (H3O)Rb3BiI7·4H2O

Abstract: Red cuboid crystals of the water‐rich iodidobismuthate(III) (H3O)Rb3BiI7·4H2O crystallize from a solution of RbI and BiIO in concentrated aqueous HI at ambient conditions. X‐ray diffraction reveale an orthorhombic structure with space group Pnma (no. 62). In the crystal structure, [BiI6]3– octahedra are arranged in layers parallel to (010). Nine‐fold coordinated Rb+ and additional I– ions connect the iodidobismuthate(III) groups into a three‐dimensional framework, which hosts protonated water complexes 1∞[H11O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The H 3 O + cation is involved only in (O)H···I bonds, which makes its role different from that in the crystal structure of (H 3 O)Rb 3 BiI 7 ·4H 2 O. In the latter, the H 3 O + cation, along with water molecules, forms a 1D (H 11 O 5 ) + polymeric cation, which takes part in interactions with Rb + cations [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The H 3 O + cation is involved only in (O)H···I bonds, which makes its role different from that in the crystal structure of (H 3 O)Rb 3 BiI 7 ·4H 2 O. In the latter, the H 3 O + cation, along with water molecules, forms a 1D (H 11 O 5 ) + polymeric cation, which takes part in interactions with Rb + cations [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The (BiI 6 ) 3− octahedra were slightly irregular, with six Bi–I bond distances ranging from 3.01 to 3.19 Å and I–Bi–I angles only slightly deviating from 90 or 180 deg ( Table 1 ). This geometry is typical for stand-alone (BiI 6 ) 3− octahedra [ 31 , 32 , 33 ]. Each of two independent I 3 - anions in the structure of 4 was symmetric ( D ih ); the I–I bond lengths were 2.92 Å in one anion and 2.95 Å in the other.…”
Section: Resultsmentioning
confidence: 99%
“…More stable hydrates are obtained when alkali metals are included, for example Li[BiI 4 ](H 2 O) 5, [7] Na 7 [BiBr 6 ][Bi 2 Br 10 ](H 2 O) 18 , [8] Na 4 [Bi 2 I 10 ](H 2 O) 14 , [9] K 4 [Bi 2 Cl 10 ](H 2 O) 4 , [10] K 4 [Bi 2 Br 10 ](H 2 O) 4 , [11] K[BiI 4 ](H 2 O), [12] Rb 5 [BiI 6 ]I(I 3 )(H 2 O) 2 [13] . or (H 3 O)Rb 3 BiI 7 ⋅ 4H 2 O [14] . Recently, Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…[13] or (H 3 O) Rb 3 BiI 7 • 4H 2 O. [14] Recently, Wang et al reported the crystallization of the solvate Cs 3 BiBr 6 • 3DMSO, which underwent a "crystal-to-crystal" transition in solution (in fact a recrystallization, not a pseudomorphosis) yielding the new tetragonal polymorph tP-Cs 3 BiBr 6 . [15] The known compounds of the pseudo-binary systems MBr-BiBr 3 have been obtained either by solid-state reaction of MBr and BiBr 3 or by precipitation from aqueous solution.…”
Section: Introductionmentioning
confidence: 99%